Penerapan Media Pembelajaran Interaktif Berbasis Game Pembelajaran Gimkit Snowbrawl untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPAS Kelas V - Simangunsong, Febiola Natasya; Wardani, Hizmi; Fatria, Fita; Tanjung, Herni Savana Br (Indo-MathEdu Intellectuals Journal, 2025)
This classroom action research aims to improve the learning outcomes of fifth-grade students in Natural and Social Sciences (IPAS) through the application of the interactive learning media Gimkit Snowbrawl. The research was conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of the research were 25 fifth-grade students of UPT SDN 060817 Medan Kota. The instruments used included learning outcome tests, student activity observation sheets, and documentation. The results of the study showed a significant increase in learning outcomes and student engagement from cycle I to cycle II. In cycle I, learning completeness reached 64%, and increased to 88% in cycle II. These findings indicate that Gimkit Snowbrawl media is effective in improving learning outcomes and student engagement in IPAS learning.